Differential Effects of Berberine and Clopidogrel on Plasma Lipid Peroxidation and Antioxidant Enzyme Activities in Male Rabbits - Fayrouz Khaled; Marwah Abdulali (AlQalam Journal of Medical and Applied Sciences, 2025)
Oxidative stress is a critical factor in the progression of cardiovascular diseases, often managed with antiplatelet therapy and natural supplements. This study investigated the effects of Clopidogrel (CLOP), Berberine (BBR), and their combination (CLOP+BBR) on the plasma antioxidant status in male rabbits. Rabbits were divided into four groups: Control, CLOP, BBR, and CLOP+BBR. Following the treatment period, plasma levels of key antioxidant markers, including Catalase (CAT), Superoxide Dismutase (SOD), and Glutathione (GSH), were measured. Additionally, Thiobarbituric Acid-Reactive Substances (TBARS) were quantified as a biomarker for lipid peroxidation. The biochemical analysis revealed that the activity of enzymatic antioxidants (CAT and SOD) and the levels of non-enzymatic GSH remained statistically unchanged (P > 0.05) across all treated groups compared to the control. In contrast, a significant reduction (P < 0.05) in plasma TBARS levels was observed in the BBR-treated group (3.272 0.036) and the combination group (3.820 0.038) relative to the control (4.578 0.024) and CLOP (4.641 0.087) groups. Clopidogrel alone did not exhibit a significant impact on lipid peroxidation or antioxidant enzyme profiles. The findings suggest that while Berberine and its combination with Clopidogrel do not significantly modulate the primary antioxidant enzyme system, they exert a significant reduction in lipid peroxidation. This highlights the potential of Berberine as a protective agent against oxidative membrane damage without interfering with the baseline antioxidant defenses.